Management Open Apex Using Bioceramic Root Repair Material : A Case Report of Permanent Anterior Teeth - Setyabudi; Yohana, Yeyen (Universitas Airlangga, 2023)
Background: Trauma to immature teeth can cause disrupt of the blood vessel supply in the pulp which leads to pulp necrosis. This can then, indirectly disrupts of root formation and incomplete apex closure.4,5 Young permanent teeth with wide open apex to be a challenge for root canal treatment, especially during obturation. Apexification is a treatment option for open apex with necrotic pulp. The purpose is to create an apical stop at the apical third of the apex so that obturation can be achieved. Case: A 27-year-old man came to RSKGMP UNAIR with chief complaints that his upper front teeth were fracture and discolored and the pain had disappeared since march 2023. From the clinical examination, tooth 21 showed Ellis fracture class III and there was tooth discoloration. Pulp vitality examination with cavity test and unresponsive k-file test, percussion (+) and bite test (+). Radiographic examination show an exposed pulp and exposed apex of tooth 21 accompanied by an unclearly defined radiolucent image at the apex of tooth 21. The diagnosis of this tooth was pulp necrosis with symptomatic apical periodontitis. Treatment: Apexification use bioceramic root repair material as apical plug at the apex. After that, obturation is achieved using a thermoplastic technique. Final restoration with individual customized post and lithium disilicate crown. Conclusion: Apexification is an option in cases of pulp necrosis with an open apex using bioceramic root repair material. Bioceramic root repair material is a bioactive material, that induces osteogenesis, is easier to apply, has faster setting time, biocompatible, hydrophilic, high pH and has anti-microbial properties.